2009
DOI: 10.1038/embor.2009.179
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular stomatitis virus inhibits mitotic progression and triggers cell death

Abstract: Vesicular stomatitis virus (VSV) infects and kills a wide range of cell types; however, the mechanisms involved in VSV-mediated cell death are not fully understood. Here we show that VSV infection interferes with mitotic progression, resulting in cell death. This effect requires the interaction of VSV matrix (M) protein with the Rae1-Nup98 complex in mitosis, which is associated with a subset of ribonucleoproteins (RNPs). VSV displaced Rae1 from spindle poles, caused spindle abnormalities and triggered substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…It is further shown that during mitosis, Rae1 in complex with Nup98, plays an essential role in mitotic spindle assembly and mitotic checkpoint regulation (Babu et al, 2003). Through binding to Rae1, VSV M protein blocks mRNA export during interphase (Faria et al, 2005; von Kobbe et al, 2000), and interferes with mitotic progression during mitosis (Chakraborty et al, 2009). Our study on ORF10 highlights the importance of Rae1 and its interaction with Nup98 in mRNA export; two viruses from very different families both target Rae1 to inhibit mRNA export.…”
Section: Discussionmentioning
confidence: 99%
“…It is further shown that during mitosis, Rae1 in complex with Nup98, plays an essential role in mitotic spindle assembly and mitotic checkpoint regulation (Babu et al, 2003). Through binding to Rae1, VSV M protein blocks mRNA export during interphase (Faria et al, 2005; von Kobbe et al, 2000), and interferes with mitotic progression during mitosis (Chakraborty et al, 2009). Our study on ORF10 highlights the importance of Rae1 and its interaction with Nup98 in mRNA export; two viruses from very different families both target Rae1 to inhibit mRNA export.…”
Section: Discussionmentioning
confidence: 99%
“…This complex can function in interphase and mitosis to inhibit mRNA export [38–42] or cause death in metaphase [43], respectively. Since tumor cells have high mitotic index, death in mitosis may contribute to VSV oncolytic function.…”
Section: Nucleoporin Action In Stress and Oncogenesis Outside The Npcmentioning
confidence: 99%
“…During mitosis, both Rae1 and Nup98 were shown to regulate spindle assembly [147,148], and VSV M protein inhibited mitosis progression via the Rae1-Nup98 complex [149]. This effect is meaningful for cancer cells, which have a high mitotic index, since VSV is an oncolytic agent that preferentially replicates and kills tumor cells rather than normal cells.…”
Section: Inhibition Of Nucleo-cytoplasmic Trafficking By Rna Virusesmentioning
confidence: 99%